PENGARUH TERPAAN TAYANGAN DHARMA WACANA BALI TV TERHADAP PEMAHAMAN UMAT MENGENAI AJARAN AGAMA HINDU DI BALI SELATAN - I Dewa Gede Agus Priana Putra; Ni Made Yuliani; Made Sri Putri Purnamawati (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
The purpose of this correlational quantitative research is to determine the exposure impact of Dharma Wacana Bali TV show (X) with the indicators of broadcasting frequency, duration and attention on the understanding people about Hinduism knowledge with the indicator of three Hindu religion framework: Tattwa, Susila and upacara. The data were collected using questionnaire with 100 respondents of Bali Selatan area. After instrument test of variable X that is exposure Dharma Wacana Bali TV show which consists of 8 questions and variable Y that is the understanding people about Hinduism knowledge which consists of 20 questions using Corrected Item-Total Correlation to 20 samples, it can be concluded that all questionnaires are valid. Likewise reliability test using Alpha Cronbach technique, both variables are reliable. So that, further testing can be done. The data were processed and analyzed using descriptive and correlations with Software IBM SPSS V.25.0 for Windows. Descriptive hypothesis testing results show that the exposure of Dharma Wacana Bali TV Shows from the sample calculation found an average of 69.69% of the expected. The results of testing the descriptive hypothesis of the understanding people about Hinduism knowledge in South Bali from sample calculations found an average of 77.74% of what was expected. Thus the third hypothesis is that there is a significant influence of the exposure of Dharma Wacana Bali TV show on the understanding people about Hinduism knowledge in South Bali.